Somatosensory source localization for the magnetoencephalography (MEG) inverse problem in patients with brain tumor - Elaina, N.S. (Institute of Electrical and Electronics Engineers Inc., 2015)
The source of the somatosensory evoked field (SEF), is one of the standard paradigm used for pre surgical mapping of brain tumor. The surgical management of the tumors requires a detailed mapping of cortical regions involved in sensory functions to avoid further deterioration of function. We investigated the early component of somatosensory evoked field (SEF) between 20-25 ms for the somatosensory response between normal and brain tumor patients and deflections in peak latency of N20M may be occurred due to present of tumor. The N20M somatosensory evoked field (SEF) corresponding electrical median nerve stimulation was measured using whole head 306 ELEKTA NeuromagÂ® MEG system. The MEG was accurately localize the origin of intraneuronal electric currents that contribute to extra cranial magnetic fields by fitting to an equivalent current dipole model (ECD). In the present study, the equivalent current dipole model is used to determine the source location of somatosensory cortex (SI) displacement due to the tumor in the central sulcus. The ECD inverse problem method had shown that the N20M SEF for unaffected hemisphere and normal subjects were located in the primary somatosensory cortex (SI) and for the affected hemisphere, the ECD source had deflected in few millimeters far from S1 cortex. We have confirmed that, the enlarged of ECD strength also occurred due to the tumor and the difference of N20M in brain tumor either in AH or UH indicated the neural pathways to the response to N20M in normal subjects might be independent. Â© 2015 IEEE.